Product Details Michelangelo: Sculptor, Painter, Architect - De Tolnay, Charles (UK Princeton, 1981)
The Description for this book, Michelangelo: Sculptor-Painter-Architect. (Vol. 1 Condensation), will be forthcoming.
Includes Illustrations and Pictures.
Keywords: Michelangelo Buonarroti, 1475-1564